2011
DOI: 10.1007/s11626-011-9429-0
|View full text |Cite
|
Sign up to set email alerts
|

Different doses of bone morphogenetic protein 4 promote the expression of early germ cell-specific gene in bone marrow mesenchymal stem cells

Abstract: Bone morphogenetic protein (BMP)-4 has a crucial role on primordial germ cells (PGCs) development in vivo which can promote stem cell differentiation to PG-like cells. In this study, we investigated the expression of Mvh as one of the specific genes in primordial germ cells after treatment with different doses of BMP4 on bone mesenchymal stem cells (BMSCs)-derived PGCs. Following isolation of BMSCs from male mouse femur and tibia, cells were cultured in medium for 72 h. Passage 4 murine BMSCs were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 24 publications
6
44
0
Order By: Relevance
“…Kee and colleagues observed that adding BMP4 at 1 ng/mL, 10 ng/mL and 100 ng/mL corresponded with a significant rise in expression of VASA [2]. Directed differentiation of bone marrow mesenchymal stem cells towards germ cells was also accompanied by significant upregulation of VASA when the BMP4 concentration was increased from 25 ng/mL to 100 ng/mL [37]. Similarly, we also observed that BMP4 had a dose-dependent effect on PGC differentiation as 50 ng/mL and 100 ng/mL BMP4 significantly upregulated …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kee and colleagues observed that adding BMP4 at 1 ng/mL, 10 ng/mL and 100 ng/mL corresponded with a significant rise in expression of VASA [2]. Directed differentiation of bone marrow mesenchymal stem cells towards germ cells was also accompanied by significant upregulation of VASA when the BMP4 concentration was increased from 25 ng/mL to 100 ng/mL [37]. Similarly, we also observed that BMP4 had a dose-dependent effect on PGC differentiation as 50 ng/mL and 100 ng/mL BMP4 significantly upregulated …”
Section: Discussionmentioning
confidence: 99%
“…PGC-directed differentiation of bone marrow mesenchymal stem cells also showed a BMP4-associated dose dependent increase in VASA expression where 100 ng/mL proved to be the best concentration compared to 25 ng/mL and 50 ng/mL [37]. A cocktail of BMPs, including BMP4, BMP7, and BMP8b supplemented at 100 ng/mL has also proven to be highly beneficial in germ cell differentiation of hESCs compared to 1 ng/mL and 10 ng/ mL of BMP4 [2].…”
Section: Impact Of Human Embryonic Stem Cellmentioning
confidence: 96%
“…This finding was inconsistent with other studies that demonstrated no effect 16, 57 or even a positive effect 43 of BMP4 on OPC proliferation. However, recent studies have suggested that the effects of BMP4 on stem cell proliferation are dose‐dependent; low dose BMP4 increases proliferation, but high dose BMP4 decreases proliferation of mesenchymal stem cells 53 or primordial germ cells 31. Considering that OPC proliferation is also affected by many factors, BMP4 may have dose‐dependent and opposite effects on OPC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were incubated in 5 mg/ml fluorescein isothiocyanate (FITC) conjugated antibodies. FITC mouse IgG2A (11-4724, eBioscience, UK) and Rat IgG1 (ab18412, abcam, USA) were used as isotype controls (Mazaheri et al, 2011;Rastegar et al, 2013). Sustentacular cells isolation.…”
Section: Methodsmentioning
confidence: 99%